(untitled) - Rafferty, Kevin (London, 1995)
This book introduce about Japan, the Once and Future Superpower. Giant among Pygmies: Yoh Kurosawa and Industrial Bank of Japan. International Flagship of Japan Inc.: Mitsubishi. The World's Biggest Steelmaker Suffers Corrosion: Nippon Steel. Kings of the Road: Toyota and the Toyodas. From Brobdingnag to Lilliput: Toshiba. Mom 'n' Pop are not Enough for Matsushita. Next Stop the Stars: Japan's Aerospace Ambitions. Japan's Miracle Children: A Hothouse Education. The Elite of the Elite: Mandarins of the Finance Ministry. Karaoke Politics: Anyone can be Prime Minister. Conclusion: Japan, Victim of its own Delusions.
Keywords: Văn hóa doanh nghiệp,Corporate culture; Nhật Bản,Japan